Bioturbation effects on metal release from contaminated sediments are metal-dependent. (July 2019) - Xie, Minwei; Simpson, Stuart L.; Wang, Wen-Xiong
Abstract: Metal flux measurements inform the mobility, potential bioavailability and risk of toxicity for metals in contaminated sediments and therefore is an important approach for sediment quality assessment. The binding and release of metals that contribute to the net flux is strongly influenced by the presence and behaviors of benthic organisms. Here we studied the effects of bioturbation on the mobility and efflux of metals from multi-metal contaminated sediments that inhabited by oligochaete worms or both worms and bivalves. Presence of bivalves enhanced the release of Mn, Co, Ni and Zn but not for copper and chromium, which is likely due to the high affinities of copper and chromium for the solid phase. Metals in the overlying water were primarily associated with fractions smaller than 10 kDa, and the fractionation of all metals were not affected by the presence of the bivalve. Metal fluxes attributed to different processes were also distinguished, and the bioturbation induced effluxes were substantially higher than the diffusive effluxes. Temporal variabilities in the total net effluxes of Mn, Co, Ni and Zn were also observed and were attributed to the biological activities of the bivalves. Overall, the present study demonstrated that the response of different metals to the same bioturbation behavior was different, resulting in distinct mobility and fate of the metal contaminants. Graphical abstract: Image 1 Highlights: Metal mobility and efflux responses to bioturbation under similar biogeochemical conditions were metal-dependent. Presence of the bivalves enhanced the release of Mn, Co, Ni and Zn from sediments. Release of Cu and Cr were not affected by bivalves due to stronger affinities for the solid phases. Bioturbation induced effluxes of metals were substantially higher than the diffusive effluxes.